Kynurenine induces T cell fat catabolism and has limited suppressive effects in vivo - Siska, Peter J.; Jiao, Jing; Matos, Carina; Singer, Katrin; Berger, Raffaela S.; Dettmer, Katja; Oefner, Peter J.; Cully, Michelle D.; Wang, Zhonglin; Quinn, William J.; Oliff, Kristen N.; Wilkins, Benjamin J.; et al. (EBioMedicine, 2021)
Background: L-kynurenine is a tryptophan-derived immunosuppressive metabolite and precursor to neurotoxic anthranilate and quinolinate. We evaluated the stereoisomer D-kynurenine as an immunosuppressive therapeutic which is hypothesized to produce less neurotoxic metabolites than L-kynurenine. Methods: L-/D-kynurenine effects on human and murine T cell function were examined in vitro and in vivo (homeostatic proliferation, colitis, cardiac transplant). Kynurenine effects on T cell metabolism were interrogated using [13C] glucose, glutamine and palmitate tracing. Kynurenine was measured in tissues from human and murine tumours and kynurenine-fed mice. Findings: We observed that 1 mM D-kynurenine inhibits T cell proliferation through apoptosis similar to L-kynurenine. Mechanistically, [13C]-tracing revealed that co-stimulated CD4+ T cells exposed to L-/D-kynurenine undergo increased β-oxidation depleting fatty acids. Replenishing oleate/palmitate restored effector T cell viability. We administered dietary D-kynurenine reaching tissue kynurenine concentrations of 19 μM, which is close to human kidney (6 μM) and head and neck cancer (14 μM) but well below the 1 mM required for apoptosis. D-kynurenine protected Rag1–/– mice from autoimmune colitis in an aryl-hydrocarbon receptor dependent manner but did not attenuate more stringent immunological challenges such as antigen mismatched cardiac allograft rejection. Interpretation: Our dietary kynurenine model achieved tissue concentrations at or above human cancer kynurenine and exhibited only limited immunosuppression. Sub-suppressive kynurenine concentrations in human cancers may limit the responsiveness to indoleamine 2,3-dioxygenase inhibition evaluated in clinical trials. Funding: The study was supported by the NIH, the Else Kröner-Fresenius-Foundation, Laffey McHugh foundation, and American Society of Nephrology.
CRIS-Team Scopus Importer:2023-03-23
Keywords: aryl hydrocarbon receptor; cancer metabolism; immunosuppression; indoleamine-2; 3-dioxygenase; T cell metabolism; tumour microenvironment